Preliminary Observations On Phytoplankton At Sacred Palustrine Habitat, Central Gujarat, India - Soni, Hiren B; Thomas, Sheju (International Journal of Environment, 2013)
The aim of the present study was to depict the phytoplankton composition of Sacred Palustrine Habitat (SPH), Anand District, Central Gujarat, India. Collections of phytoplankton were carried out at three permanent sampling stations on monthly basis for one year (June 2012 to May 2013). The phytoplankton population was represented by 39 genera and 48 species belongs to family Bacillariophyceae (21 species), followed by Cyanophyceae (7 species), Cholorophyceae (18 species), and Euglenophyceae (2 species). Species such as Ankistrodesmus convolutus Corda, Closteriopsis longissima Lemmermann, Oscillatoria perornata Skuja, Oscillatoria subbrevis Schmidle, Syndrea ulna (Nitzsch) Ehrenberg, were found abundant at all the study sites, while some species were rare 56.25% (n=27). International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 115-126 DOI: http://dx.doi.org/10.3126/ije.v2i1.9215